2020
DOI: 10.2147/opth.s265647
|View full text |Cite
|
Sign up to set email alerts
|

<p>Contribution of Posterior Corneal Astigmatism to Total Corneal Astigmatism in a Sample of Egyptian Population</p>

Abstract: Purpose: To determine the percentage of contribution of the magnitude of posterior corneal astigmatism to total corneal astigmatism using Scheimpflug imaging. Methods: This prospective cross-sectional study was conducted on 356 eyes of 356 patients, where the total corneal astigmatism was calculated by addition of anterior and posterior corneal astigmatism using vector analysis and then the percentage of posterior to total corneal astigmatism was calculated. Results: The percentage of contribution of posterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…reported that the PCA was 0.11 ​± ​0.24 D in the ATR eyes contributing to 8% to the TCA, which is less compared to our result. 12 This discrepancy may be due to the fact that the patients enrolled in their study were younger population aged from 18 to 45 years old. As various studies had established that the ACA gradually shifted from WTR to ATR while the change of the posterior surface of the cornea is much less.…”
Section: Discussionmentioning
confidence: 93%
“…reported that the PCA was 0.11 ​± ​0.24 D in the ATR eyes contributing to 8% to the TCA, which is less compared to our result. 12 This discrepancy may be due to the fact that the patients enrolled in their study were younger population aged from 18 to 45 years old. As various studies had established that the ACA gradually shifted from WTR to ATR while the change of the posterior surface of the cornea is much less.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have shown that ignoring the posterior corneal surface may lead to inaccurate estimation of total corneal power and astigmatism in some eyes. [1][2][3][4] Even though the K value considers the effect of PCA in calculations using mathematical extrapolation, these methods do not consider outliers and irregularities into account. [5][6][7] The latest modalities, such as Pentacam, Galilei, and IOLMaster 700, allow obtaining TCRP via direct measurement instead of estimating the posterior corneal curvature, which is a promising tool for determining toric IOL cylinder power.…”
Section: Discussionmentioning
confidence: 99%
“…However, over the past few years, the effect of posterior corneal astigmatism (PCA) during toric intraocular lens (IOL) implantation has received considerable attention. [1][2][3][4] One of the strategies to minimize the effects of PCA is to optimize K astigmatism using nomograms, 5 regression equations, 6 or mathematical models. 7 However, these methods are based solely on mathematical extrapolation and do not consider individual differences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the application of toric and presbyopia-correcting intraocular lens (IOL, toric IOL and PC-IOL), precise assessment of preoperative corneal astigmatism (CA) has played an increasingly important role in the past twenty years [1][2][3][4]. The larger the CA, the poorer the postoperative visual acuity at all distances after implantation of either monofocal or multifocal IOLs [5,6].…”
Section: Introductionmentioning
confidence: 99%